Hubungan Metakognitif, Kemampuan Berpikir Kritis, Bimbingan Orang Tua dan Guru tentang Kesehatan Reproduksi dengan Persepsi Perilaku Seksual Siswa SMA Se-Kota Medan - Alfi Sapitri; Ely Djulia; Herbert Sipahutar (Magister Pendidikan Biologi, Universitas Negeri Medan, 2018)
This research intended to identify: (1) Student metacognition about reproduction health, (2) student critical thinking skill about reproduction health; (3) Student perception of sexual behaviour, (4) Parents’ and teachers’ guidance about reproduction health, (5) Teachers’ guidance about reproduction health, (6) The correlation among metacognitive, critical thinking, parents’ and teachers’ guidance about reproduction health into perception of sexual behaviour. This correlation study was conducted at Senior high schools in district Medan, North Sumatra Indonesia at 2013 academic year. Research instruments consist of metacognitive knowledge, metacognitive skill, critical thinking, parents’ and teachers’ guidance, and student perception of sexual behaviour that had been tested for validation, reliability, differential index and difficulty level. Data were analyzed through applied correlation analysis by using SPSS 21.0 for windows. The result of this study indicated that: (1) student metacognitive knowledge are moderately categorized as urban and rural while metacognitive skill are highly categorized for urban and rural; (2)student’s critical thinking are classified as moderate in urban and rural; (3) the student’s perception of sexual behaviour are moderate urban and rural;(4) parents’ guidance contributed moderately in urban and rural; (5) teachers’ guidance contributed moderately in urban and lowly in rural; (6) there is significant correlation between student perception of sexual behaviour and metacognition, critical thinking skill, parents’ and teachers’ guidance about reproduction health with Sig 0,049 < 0,05.